Kajian Semiotika Roland Barthes Pada Poster Workshop Bulanan Wayang Merdeka Pada Tema “Berkarya, Belajar, Dan Berbagi” - Lejar Daniartana Hukubun (Kartala Virtual Studies, 2026)
Abstract A poster is one of the most effective visual communication design works for conveying messages to an audience. An engaging poster is supported by various components such as illustration, typography, color, readability, white space, and other visual elements. Beyond functioning as a medium of information delivery, a poster can also be explored further to uncover deeper meanings using Roland Barthes’ semiotics, allowing us to interpret layers of meaning through denotation, connotation, and myth. At the denotative level, the poster presents an art community with a spirit of service, education, and collaboration. At the connotative level, it evokes creativity, communal closeness, and cultural preservation. At the level of myth, the poster constructs a broader narrative about the continuity of local culture through activities of collective learning, knowledge sharing, and dissemination of information related to the Wayang Merdeka Community. This journal emphasizes that a poster is not merely an informational medium, but also a producer of meaning that strengthens the community’s identity and encourages society to take part in preserving wayang culture. Keywords: Wayang Merdeka Community, Denotation, Connotation, Myth, Roland Barthes’ Semiotics.